2022
DOI: 10.3390/ijms231911005
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Obesity in Humans: A Clinical Review

Abstract: Obesity is a complex multifactorial disorder with genetic and environmental factors. There is an increase in the worldwide prevalence of obesity in both developed and developing countries. The development of genome-wide association studies (GWAS) and next-generation sequencing (NGS) has increased the discovery of genetic associations and awareness of monogenic and polygenic causes of obesity. The genetics of obesity could be classified into syndromic and non-syndromic obesity. Prader–Willi, fragile X, Bardet–B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 99 publications
0
33
0
Order By: Relevance
“…This difference may be due to more weight loss opportunities for females than males. (12,13) Previous findings also document more weight loss among females than males. ( Contradictory 14,15,16,17) findings were reported in Retrofit study population where males experienced more weight loss than females.…”
Section: Discussionmentioning
confidence: 94%
“…This difference may be due to more weight loss opportunities for females than males. (12,13) Previous findings also document more weight loss among females than males. ( Contradictory 14,15,16,17) findings were reported in Retrofit study population where males experienced more weight loss than females.…”
Section: Discussionmentioning
confidence: 94%
“…This leads to leptin resistance, and the underlying mechanisms are diverse, including impaired ObRb signaling, changes in hypothalamic neural wiring, reduced brain leptin transport and ObRb trafficking, endoplasmic reticulum stress, and, frequently, low-grade inflammation [ 143 ]. Through genome-wide association studies and next-generation sequencing, approximately 500 obesity-related genes were identified, with mutations in some of these genes, including leptin and its receptor genes, POMC, MC4R, BDNF, prohormone convertase 1, unique homologue 1, and neurotrophic receptor tyrosine kinase type 2, having been reported to cause obesity [ 144 ]. In this section, the first two will be described.…”
Section: Functionality Of Leptin and Its Involvement In Pathologymentioning
confidence: 99%
“…NTRK2 is a neurotropin (NT-3) receptor that is critical for neuronal development. Mutations in this gene result in obesity 30 and mood disorders 31 . PRKCA codes for protein kinase C-alpha 32 that has been associated with ASD 33 , while TEK codes for TIE2, and is expressed almost exclusively in the vascular system 34 .…”
Section: Genetic Variants and Differentially Expressed Genes In The A...mentioning
confidence: 99%